Review: Saskia Stucki, One Rights: Human and Animal Rights in the Anthropocene - Eva Bernet Kempers (Journal of Animal Law, Ethics and One Health)
Animal rights law is in need of an update. Many of its central theories were developed over 20 years ago, meaning that they fail to take account of issues that, in today’s society, are inextricably linked to the question of animal rights. Conspicuously absent in this regard is the relevance of the current climate change emergency. Saskia Stucki’s recent book ‘One Rights: Human and Animal Rights in the Anthropocene’ aims to put animal law in its contemporary context by framing animal rights as a new generation of human rights, proposing a novel paradigm of ‘One Rights’ for the Anthropocene. With its sharp and in-depth engagement with animal law literature, as well as human rights law scholarship, it provides a much-needed and nuanced view of animal rights in the 21st century.